Educational leadership in an online world: connecting students to technology responsibly, safely, and ethically - Ribble, Mike; Miller, Teresa N. (My University, 2013)
The current gap in technology knowledge and lack of leadership preparation related to digital literacy for school environments can cause serious problems, as school leaders, parents, and broader social communities are currently realizing. The authors describe strategies for educational leaders to prepare their stakeholder groups for a digital future, as well as take actions to reduce technology misuse or abuse. Educational institutions should consider this Digital Citizenship model as a potential new tool to for students, faculty and staff—both on-site and online.
Keywords: Etiquette; Citizenship; Educational leadership; Digital Citizenship; Digital literacy